The impact of Covid-19 on the port environment: The case of Tanger Med container port, Morocco - Abous Hajar; Hamiche Mhamed; El Merouani Mohamed (E3S Web of Conferences, 2021)
The appearance of the COVID-19 virus has a huge impact on the economy, where many factories and logistics flows are affected. With global supply chains severely disrupted, production and consumption centers around the world are beginning to be affected by the situation. our study tried to measure the impact of this pandemic on the containers transport in Morocco, our work targeted the Tanger Med port due to its geographic position as the most important link between Africa and Europe, Autoregressive Distributed Lag (ARDL) cointegration technique was applied, this model integrates the term of lag and difference in the modeling of linear series. To verify the existence of long-term relationships, F-bond test was applied. The model was estimated on short and long term. the results were significant and has shown that the activity within Tanger Med port, experienced a shock during the pandemic period.